Efeitos da exposição ao glifosato sobre parâmetros comportamentais em peixe-zebra (Danio rerio) - Bridi, Daiane (2017)
Glyphosate has become the most widely used herbicide in the world, due to the wide scale adoption of resistant crops, after its introduction in 1996. Glyphosate can be used alone, but is commonly used as an active ingredient of the Roundup® herbicide. This herbicide contains several adjuvants in addition to glyphosate, which may promote an unknown e.g. toxicity Polioxietilenamida (POEA). Zebrafish is gaining popularity in behavioral research, because of its physiological similarity to mammals, ease of manipulation, robust performance, low cost, external fertilization, transparency of embryos larval stages and rapid development. The aim of this study was to evaluate the effects of glyphosate and Roundup® on behavioral and morphological parameters in zebrafish larvae and adult. Zebrafish larvae at 3 days post-fertilization (dpf) and adults were exposed to glyphosate (0.01, 0.065, and 0.5 mg/L) and Roundup® (0.01, 0.065, and 0.5 mg/L) for 96 hours. Immediately after the treatment, behavioral parameters such as locomotor activity and aversive behavior and morphology for the larvae and locomotion, agressive behavior and memory for the adults were analyzed. Zebrafish larvae, the results indicated that there were significant differences in the locomotor activity and aversive behavior by glyphosate and Roundup® when compared to the control. However, there was a decrease in distance traveled and the time spent in zone without stimulation for exposed larvae at doses of glyphosate and Roundup®. A significant decrease in body lenght was observed for larvae exposed to Roundup® in all concentrations tested. Our findings demonstrated that glyphosate and Roundup® exposure reduced the distance traveled, the mean speed and the line crossings in the highest concentration of glyphosate (0.5 mg / L) and 0.065 and 0.5mg/L Roundup® in animals adults. We verified that Roundup®-treated adult zebrafish showed a significant impairment in memory. Our results showed that glyphosate and Roundup® had an effect on agressive behavior. Our findings demonstrated that the effects of isolated and commercial forms of glyphosate promoted differences on locomotion, behavior and morphology of the treated animal, suggesting similar mechanisms of toxicity and cellular response.